Determination of the suitable drilling operating parameters in different geological formations El-Sharara Oil Field (South-Western Libya) - Sayed, M; Boghdady, G; Abdellah, W (National Mining University, 2018)
Purpose. The objective of this study is to determine the best operating conditions for the most notable drilling parameters (i.e. weight on bit (WOB), rotary drilling speed (RPM), and characteristics of drilling fluid) using field data obtained from El-Sharara Oil Field. Methods. The used data has been extracted from daily drilling reports of well named (NC-186/K04h) field. Such data contains information about the geological formations, casing strings, drill-bits, fuel consumption, flow rate of drilling fluid and other drilling parameters. Findings. The results reveal that, the lower geological formations of El-Sharara Oil Field, the harder are the upper formations. Therefore, it is recommended to apply heavy loads (i.e. WOB of 45000 lb) with low drilling speed (i.e. 100 rpm) in the lower formations; and to apply small loads (i.e. WOB of 19000 lb) with high drilling speed (i.e. 160 rpm) in the upper formations. Originality. This study evaluates the performance of drilling operation based on the interaction between rock formations and machine drilling parameters. Practical implications. Understanding such interaction between rock formations and machine drilling parameters will remarkably improve the rate of penetration (ROP) in the related geological formations. Consequently, the overall drilling costs will be reduced in terms of drilling time, life of drill-bit and fuel consumption.

Мета. Визначення оптимальних експлуатаційних умов для технологічних параметрів буріння – осьового навантаження на долото (ОНД), швидкості обертального буріння (ШOБ), характеристик бурового розчину на основі емпіричних даних, отриманих на нафтовому родовищі Ель-Шарара. Методика. У роботі вивчені та систематизовані дані експлуатації нафтової свердловини NC-186/K04h, що містять інформацію про геологічні формації родовища, обсадних колонах, бурових коронках, витрат палива і бурової рідини та інших параметрах буріння. Результати. Дослідження показало, що, чим нижче розташовані нафтоносні геологічні формації Ель-Шарара, тим міцніше породи верхніх формацій. Рекомендовано застосовувати велике навантаження (ОНД – близько 104 кг), при низькій ШOБ (100 об/хв) у нижніх формаціях; і мале навантаження (ОНД – 86 кг) при високій ШOБ (160 об/хв) – у верхніх формаціях. Встановлено кореляційний взаємозв’язок комплексу технологічних параметрів буріння з умовами геологічних формацій родовища. Наукова новизна. Для умов нафтового родовища Ель-Шарара дана наукова оцінка ефективності буріння на основі встановлення взаємозв’язку параметрів формацій і бурових установок. Практична значимість. Врахування взаємозв’язку геологічних формацій і параметрів механічного буріння дозволить суттєво підвищити швидкість проходки свердловин, при цьому загальні витрати на буріння будуть скорочені за рахунок зменшення часу буріння, споживання палива та збільшення терміну служби бурових коронок.

Цель. Определение оптимальных эксплуатационных условий для технологических параметров бурения – осевой нагрузки на долото (ОНД), скорости вращательного бурения (СВБ), характеристик бурового раствора на основе эмпирических данных, полученных на нефтяном месторождении Эль-Шарара. Методика. В работе изучены и систематизированы данные о эксплуатации нефтяной скважины NC-186/K04h, которые содержат информацию о геологических формациях месторождения, обсадных колоннах, буровых коронках, расходе топлива и буровой жидкости, а также других параметрах бурения. Результаты. Исследование показало, что, чем ниже расположены нефтеносные геологические формации Эль-Шарара, тем тверже породы верхних формаций. Рекомендуется применять большую нагрузку (ОНД – около 104 кг), при низкой СВБ (100 вр/мин) в нижних формациях; и малую нагрузку (ОНД – 86 кг) при высокой СВБ (160 вр/мин) – в верхних формациях. Установлена корреляционная взаимосвязь комплекса технологических параметров бурения с условиями геологических формаций месторождения. Научная новизна. Для условий нефтяного месторождения Эль-Шарара дана научная оценка эффективности бурения на основе установления взаимосвязи параметров формаций и буровых установок. Практическая значимость. Учет взаимосвязи геологических формаций и параметров механического бурения позволит существенно увеличить скорость проходки скважин, при этом общие затраты на бурение будут сокращены за счет уменьшения времени бурения, потребления топлива и увеличения срока службы буровых коронок.
Keywords: improvement of drilling operation; operating parameters; rock properties; oil well drilling; El-Sharara Oil Field